Dosimetric comparison of carbon ion and X-ray radiotherapy for Stage IIIA non–small cell lung cancer. (30th September 2016) - Kubo, Nobuteru; Saitoh, Jun-ichi; Shimada, Hirofumi; Shirai, Katsuyuki; Kawamura, Hidemasa; Ohno, Tatsuya; Nakano, Takashi
Abstract: The present study compared the dose–volume histograms of patients with Stage IIIA non–small cell lung cancer (NSCLC) treated with carbon ion radiotherapy with those of patients treated with X-ray radiotherapy. Patients with Stage IIIA NSCLC ( n  = 10 patients for each approach) were enrolled. Both radiotherapy plans were calculated with the same targets and organs at risk on the same CT. The treatment plan for the prophylactic lymph node and primary tumor (PTV1) delivered 40 Gy for X-ray radiotherapy and 40 Gy (relative biological effectiveness; RBE) for carbon ion radiotherapy. The total doses for the primary tumor and clinically positive lymph nodes (PTV2) were 60 Gy for X-ray radiotherapy and 60 Gy (RBE) for carbon ion radiotherapy. The homogeneity indexes for PTV1 and PTV2 were superior for carbon ion radiotherapy in comparison with X-ray radiotherapy (PTV1, 0.57 vs 0.65, P  = 0.009; PTV2, 0.07 vs 0.16, P  = 0.005). The normal lung mean dose, V5, V10 and V20 for carbon ion radiotherapy were 7.7 Gy (RBE), 21.4%, 19.7% and 17.0%, respectively, whereas the corresponding doses for X-ray radiotherapy were 11.9 Gy, 34.9%, 26.6% and 20.8%, respectively. Maximum spinal cord dose, esophageal maximum dose and V50, and bone V10, V30 and V50 were lower with carbon ion radiotherapy than with X-ray radiotherapy. The present study indicates that carbon ion radiotherapy provides a more homogeneous target dose and a lower dose to organs at risk than X-ray radiotherapy for Stage IIIA non–small cell lung cancer.